Perceived Usefulness, Perceived Enjoyment, Trust, and Continuance Intention - Chen, Yong See Chen; Yue, Sun (International Journal of Psychosocial Rehabilitation, 2020)
Users consistency in using mobile apps has become significantly important for the app- related technology development. The aim of this paper is to investigate the effects of perceived usefulness, perceived enjoyment, and trust on the users’ continuance intention to use mobile apps. This paper proposed a research framework to identify the predictors of continuance intention of mobile apps users and highlight the users experience when using mobile apps. Data were collected from mobile apps users in Malaysia. This study used structural equation modeling (SEM) with AMOS statistical software to test the research framework using a standardized and structured self-administered questionnaire. The results generate suggestions for mobile apps developers to prioritize perceived enjoyment, and trust in their planning to retain their users to continuously using the mobile apps. Although many studies have focused on continuance intention, but, still lack of studies have examined the behavior of individual differences based on demographics, such as continuance intention of mobile apps users in Malaysia. It generates useful guidance for mobile apps developers, specifically, aims on mobile apps users in Malaysia to effectively retain them in using their mobile apps.